Corruption and Ports Management: Case of Beirut Port Blast - Salem Y. Lakhal; Camelia Lakhal (International Journal of Supply Chain Management, 2021)
Corruption in ports where many players are working in an environment of a conflicting interest is a perennial problem. This paper argues that internal controls by the ports authorities will be affected by corruption which puts at risk the facilities and the persons. The issues are illustrated with the Lebanon port case where a gigantesque blast took place in July 2020. It is argued that the corruption affected severely the adequate management of the facilities of the port and limits the possibilities of preventing the accident. This paper verifies some hypotheses using publications that addressed the issue before and after the ballast. Our search included peer-reviewed literature, witness journalist reports, politician interviews, reports published by international organizations, and some media articles. Our finding is that the corruption has infiltrated the port of Lebanon and the blast is a logical result of the lack of the control at many levels.  What is more, it is appear that the corruption is not to be limited to the port, but it affects also some level of government or type of authorities. Finally, anti-corruption, transparency and accountability mechanisms is difficult to instore in a country where the arms are diluted on the hands of many factions and ravaged by many years of war.